Ultrasound-guided Deep Waist Fat Liposuction: Complement to a Narrow Waist - Emmanuel Armando Flores González, MD; Raúl Martin Manzaneda Cipriani, MD; Ricardo Babaitis, MD; Héctor Durán Vega, MD; Mauricio Schneider Viaro, MD; Daniel Lobo Botelho, MD; Stefan Danilla Enei, MD; Oliver René Ramirez Guerrero, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. For body contouring, the waist plays an important role in both male and female body structure. Currently, there are procedures that aim to achieve a narrow waist as a result, to achieve an adequate waist-to-hip ratio. This study proposes a technique of ultrasound-guided deep liposuction of the lumbar triangle to achieve favorable and safe aesthetic results. Methods:. The technique was applied in 142 patients who provided informed consent. During liposuction, ultrasound was used as a guide to avoid contact with vital organs, and in the postoperative stage, a satisfaction survey was administered on the aesthetic results obtained. In addition, patients had a preoperative waist measurement and a postoperative waist measurement at 3 months. Results:. The deep liposuction technique in the lumbar triangle is safe, no serious complications were observed, and the results of the satisfaction survey regarding the aesthetic result after the third postoperative month showed 100% satisfaction. In addition, it was found that the body measurements of the waist before the operation and 3 months later showed a difference between 8 and 15 cm less in the diameter of the waist after the technique was applied. Conclusions:. Deep liposuction of the lumbar region is a safe technique, due to the use of ultrasound for patient care, and enhances patient satisfaction with the aesthetic results.